Financial Stimulation of Forest Resources Deep Processing - ZOZULYA, Valentina Vladimirovna; ROMANCHENKO, Olga Viktorovna; ZUYKOV, Andrey Vladimirovich; SERGEEVA, Anastasiya Yurievna; MEDVEDEV, Sergey Olegovich; ZOZULYA, Inga Vladimirovna (Journal of Advanced Research in Law and Economics; Vol 8 No 1 (2017): JARLE Volume VIII Issue 1 (23) Spring 2017, 2017)
The article deals with the economic problems of forest resources deep processing. The main aim of the research is to discover some financial ways to develop effectiveness of processing industry activities in forest complex. The results achieved in the study are the authors’ proposals to improve the economic component of forest raw materials processing at stages of production and trade. The financial instruments to develop deep raw materials processing of forest resources can be arranged in this order according to the criteria of effectiveness: investment tax credit; tax holidays in some cases; lower VAT rates on the production of forestry; tax benefits set into corporate income taxes based on reinvestment of profit terms; tax exemption in respect of corporate property taxes; lower credit rates for the projects in non-investment banks; special non-tax investment credit lines; public private partnership; special financing of certain programs or projects; higher customs duties for raw materials export and lower – for processing. On the basis of mentioned financial instruments we prepared Model of financial stimulation of processing industry in forest complex.